Wave characteristics around perforated piles in a two rows arrangement - Mohd. Anuar, Norzana (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2012)
An experimental study was performed to investigate the transmission response of a two-row perforated double ring pile (DP). The tests were conducted in unidirectional waves with different wave conditions and pile porosity that varied from 0.0625 to 0.48. From the experimental results, it was found that when the pile porosity increases, less wave energy was attenuated, resulting in higher wave transmission coefficient, Kt. Furthermore, Kt was found to be decreasing when the wave steepness increases for all porosity values. Moreover, higher water depth has higher Kt especially at low relative depth range between 0.1 and 0.15 with Kt being more than 0.3 at a water depth h ≤ 0.27 m and Kt was more than 0.60 when h ≥ 0.3 m. Tests on spacing B and model width W were also investigated. Wider spacing (B ≥ 0.5D) resulted in lower wave attenuation, whilst wider model of more than one row generally attenuated more wave energy as expected. However the percentage of attenuation of the model system with more than two-rows tends to be ineffective, thus indicating that the test model with a width W>2D has less influence in attenuating waves. An empirical equation to predict transmission coefficient was also derived based on statistical analyses using independent wave parameters namely relative depth (h/L), wave steepness (Hi/L), relative model spacing (B/L) and model porosity (). A multiple linear regression analysis was used to model the relationship of these variables. Comparisons of transmitted wave performance by other researchers were also analyzed.